CBDC: Banking and anonymity - Yuteng Cheng; Ryuichiro Izumi (Bank of Canada, 2024)
We examine the optimal amount of user anonymity in a central bank digital currency (CBDC) in the context of bank lending. Anonymity, defined as the lender's inability to discern an entrepreneur's actions that enable fund diversion, influences the choice of payment instrument due to its impact on a bank's lending decisions. We show that moderate anonymity in CBDC leads to an inefficient pooling equilibrium. To avoid this, CBDC anonymity should be either low, reducing attractiveness, or high, discouraging bank lending. Specifically, the anonymity should be high when CBDC significantly benefits sales, and low otherwise. However, competition between deposits and CBDC may hinder the implementation of low anonymity.
Keywords: E42; E58; G28; 330; Digital currencies and fintech